Digital silk road : digital archives of cultural heritage - Kokuritsu Jōhōgaku Kenkyūjo (2003)
[Dt.:] Digital Silk Road ist ein Projekt des japanischen National Institute of Informatics. Es versucht, verschiedene bereits bestehende digitale Archive und Ressourcen zum Thema Seidenstraße zusammenzufassen. Neues Archivmaterial soll durch die Zusammenarbeit leichter erschlossen und einem größeren Publikum zugänglich gemacht werden. Sowohl Karten als auch Bilder und Bücher sind somit als Digitalisate online zugänglich. - [Engl.:] Digital Silk Road Project is a research project to realize these goals by integrating information technology with the study of culture. To be specific, it must be investigate various methods, starting from the digitization of real cultural artifacts, and the construction of digital archives, to the exhibition of digital cultural resources over the network and annotation to digital cultural resources based on collaborative work. The website provides access to maps, pictures and e-books about the Silk Road topic.